2006
DOI: 10.1007/s00345-006-0105-z
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term results of standard procedures in urology: the ileal neobladder

Abstract: Over the past 20 years orthotopic urinary reconstruction with the techniques developed at Ulm and Bern has become a widely accepted form of urinary diversion. So far, both centers together have performed more than 1,300 orthotopic bladder substitutions with an overall rate of neobladder formation in 58% of all cystectomized patients. Today, the absolute contraindications for this procedure are urinary stress incontinence, damaged rhabdosphincter, severely impaired renal and liver function, severe intestinal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(70 citation statements)
references
References 53 publications
2
63
1
4
Order By: Relevance
“…There is few literature comparing post-op neobladder function after radical cystectomy between LRC and ORC and only four studies in Chinese were identified, in which three studies adopted orthotopic neobladder reconstruction and one study had ileal conduit. Our included three studies reported daytime continence rates of 91%, 94%, 92% and a nighttime rate of 88%, 82%, 78% respectively, and compared favourably with previously reported values in other single LRC series daytime rate (89–98%) and nighttime rate (78–88%) [46][48]. In the present meta-analysis, Qmax, neobladder capacity, IVP, RUV, day time and night time continence rate were similar in the two groups, which demonstrated the efficacy of LRC in post-op neobladder function.…”
Section: Discussionsupporting
confidence: 90%
“…There is few literature comparing post-op neobladder function after radical cystectomy between LRC and ORC and only four studies in Chinese were identified, in which three studies adopted orthotopic neobladder reconstruction and one study had ileal conduit. Our included three studies reported daytime continence rates of 91%, 94%, 92% and a nighttime rate of 88%, 82%, 78% respectively, and compared favourably with previously reported values in other single LRC series daytime rate (89–98%) and nighttime rate (78–88%) [46][48]. In the present meta-analysis, Qmax, neobladder capacity, IVP, RUV, day time and night time continence rate were similar in the two groups, which demonstrated the efficacy of LRC in post-op neobladder function.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the cost of the procedure must also be taken into account (7). As there is no single option suitable for every patient, it is important to know and consider the different diversion methods.…”
Section: Discussionmentioning
confidence: 99%
“…Large retrospective non-selected series from single institutions have shown that the recurrence-free survival (RFS) rates following RC ranges from 62% to 68% and 50% to 66% at 5 years and 10 years, respectively (3-5). Moreover, Hautmann et al published similarly long-term oncologic outcomes among 1,100 patients who underwent RC; they exhibited an overall 10-year cancer-specific survival (CSS) rate of 67% (6).…”
mentioning
confidence: 99%